Precise monitoring and complication control for the patients with neurosurgical critical illness can improve their clinical prognosis - Ning WANG; Xin QU (Chinese Journal of Contemporary Neurology and Neurosurgery, 2020)
DOI：10.3969/j.issn.1672⁃6731.2020.08.001